Senior first, junior second. Issue 1 (19th September 2021) - Gunawan, Joko; Marzilli, Colleen
Abstract: The seniority system exists in most companies, including in healthcare industries. Seniority often plays an essential role in the organizational success and career advance of employees. However, there are pros and cons in the application of the seniority system in all organizations, especially in the healthcare industry. This article prompts a discussion about seniority in nursing and provides some particular concerns and recommendations for consideration, and this begs the question, should senior be first and junior second?